PROSES REGENERASI SIRIP EKOR PADA IKAN KRAPU DI LABUHAN BATU - SUMARNY PURBA (JURNAL ILMIAH MAKSITEK, 2019)
Krapu fish fin in Labuhan Batu as a model for regeneration studies both in terms of process and molecular analysis studies. This research is a descriptive exploratory study. Krapu fish samples in Labuhan Batu (Danio rerio) aged 4-6 months were 30 individuals. The tail fin regeneration of Krapu fish in Labuhan Batu was observed under a microscope by cutting vertically. The parameters observed were: 1) the time needed for the regeneration process, 2) The regeneration process in detail includes and, 3) the type of regeneration. Data in the form of the regeneration process from wound healing to the original length obtained was collected in the form of digital photographs. The results showed that the time needed to regenerate the tail fin to recover to normal at temperatures 22-31 ° C was 22.25 ± 1.63 days for the vertical cut model. The regeneration process begins with the event of wound healing (H1) followed by the formation of the blastema and the radius of the will (H2) and continued differentiation marked by the process of angiogenesis (H2). Regenerative development begins with the formation of the radius and growth of the peripheral region so that the caudal fin is faster than the medial region (H3-H8). The final regeneration process in the Krapu fish tail fin in Labuhan Batu which is included in the development is the formation of the regenerative segment radius from proximal to the distal regenerate regenerate (H9 - H21). From the results of this study it is known that the tail fin Krapu in Labuhan Batu can regenerate epimorphosis.